2018
DOI: 10.1002/cssc.201801641
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic‐Framework‐Derived Co3S4 Hollow Nanoboxes for the Selective Reduction of Nitroarenes

Abstract: MOF-derived Co S /CN hollow nanoboxes (CN=nitrogen-doped carbon) was used to catalyze the chemoselective reduction of nitroarenes to anilines under mild reaction conditions with H as the reducing agent. The catalyst provides high conversion efficiencies and selectivities for a variety of nitroarene substrates that contain electron-donating or electron-withdrawing substituents under mild reaction conditions (in methanol at 60 °C). Further, the nanobox inhibits both dehalogenation and vinyl hydrogenation reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 82 publications
4
21
0
Order By: Relevance
“…nitro-compounds hydrogenations,244,263,276,280,281,285,[304][305][306][307] alcohols oxidations,247,293,297 CO oxidation250,259,[264][265][266][267][268][277][278][279]289,[294][295][296]301,246,254,285,[290][291][292]309,310 Ox, achieved by the direct calcination of a bimetallic Ce(Cu)-MOF at 600 °C for 3 h. The catalytic activity was tested using a continuous flow fixed-bed micro-reactor at atmospheric pressure with a CO/O2/N2 mixture in a volume ratio of 1:10:89. The authors found the CeO2-CuO exhibited a high catalytic activity in comparison to that of Ce-Cu-Ox; an almost 80% CO conversion for CeO2-CuO at 250 °C and only 22% for Ce-Cu-Ox derived from the Ce(Cu)-MOF.…”
mentioning
confidence: 99%
“…nitro-compounds hydrogenations,244,263,276,280,281,285,[304][305][306][307] alcohols oxidations,247,293,297 CO oxidation250,259,[264][265][266][267][268][277][278][279]289,[294][295][296]301,246,254,285,[290][291][292]309,310 Ox, achieved by the direct calcination of a bimetallic Ce(Cu)-MOF at 600 °C for 3 h. The catalytic activity was tested using a continuous flow fixed-bed micro-reactor at atmospheric pressure with a CO/O2/N2 mixture in a volume ratio of 1:10:89. The authors found the CeO2-CuO exhibited a high catalytic activity in comparison to that of Ce-Cu-Ox; an almost 80% CO conversion for CeO2-CuO at 250 °C and only 22% for Ce-Cu-Ox derived from the Ce(Cu)-MOF.…”
mentioning
confidence: 99%
“…While TBHP-driven oxidations of arylmethanes have been reported to be catalyzed by Fe-N-C materials effectively, 23,[27][28][29] the cobalt corresponding Co-N-C catalysts were not. 30 Typically, Co-N-C catalysts are used for reduction reactions (nitroarenes, 31,32 N-heterocycles, 33 and hydrocarbons 34 ), reductive aminations 35 and alkylations, 36,37 while the oxidative esterification of benzyl alcohols were done under dioxygen. [38][39][40] Overall, the cobalt materials outperformed the three previously reported related Fe-N-C systems (TAL-1-900, TAL-6-900, TAL-7-900), 22,23 and importantly, they sustained their activity over a larger number of cycles (Fig.…”
Section: Morphological and Physical Characterizationsmentioning
confidence: 99%
“…8,12,13,[15][16][17][18][19][20] Developing new hydrogenation catalysts with high intrinsic chemoselectivity is a straightforward and effective strategy to tackle this tough problem. 8,[21][22][23][24][25][26][27] Some important progresses have been achieved recently by employing Au-, Ag-based, and pyrolyzed Fe(or Co)/nitrogen/carbon catalysts for selective reduction of the nitro group of substituted nitroarenes. 8,21,25,[28][29][30] Nevertheless, these catalysts always suffer from low activity and thus often require harsh reaction conditions, such as high temperature (≥120 °C), high H 2 pressure (≥5.0 MPa), and long reaction time (≥12 h).…”
Section: Introductionmentioning
confidence: 99%